Polarization-adjustable color reflector based on Fano resonance - Junyang Zhu; Qi Wang; Ruimei Zeng; Yiqun Zhou; Ruijin Hong; Dawei Zhang (AIP Advances)
This paper presents a polarization-adjustable color reflector utilizing Fano resonance, enabling full color control through the manipulation of the polarization angle of the incident light. The reflector integrates a broadband filter with a narrowband filter, while the T-shaped aluminum (Al) microstructure in the top layer facilitates tunable reflection spectra. By varying the polarization angle of the incident light (TM/TE), two distinct colors (yellow and blue) can be exhibited, achieving a color difference ΔE2000 of up to 75.9 with high color purity, and the peak reflectance reaching 72% and 50%, respectively, thereby demonstrating the great polarization modulation capabilities of the color reflector. By adjusting the thickness of the silicon (Si) dielectric layer, reflection colors can vary widely from magenta to green. Notably, high-saturation green is reflected when the Si layer thickness is set to 35 nm, indicating potential for applications in full-color gamut display. A deep neutral network model is utilized to optimize the structural parameters. The optimized Fano resonance optical coating design achieves peak reflectance reaching 87% (TM) and 56.6% (TE) while maintaining good color saturation. Furthermore, the reflector exhibits good angular insensitivity, maintaining a maximum color difference ΔE2000 of 5.0 when the incident angle is <30°. In addition, the physical mechanism of high reflectivity and saturation in yellow is revealed through electric field distribution analysis under TM incident light. The polarization-adjustable color reflector based on Fano resonance holds potential applications in dynamic color displays and anti-counterfeiting labels.